Confocal luminescence investigations of two-beam direct-uv-written silica-on-silicon waveguides - Adikan, Faisal Rafiq Mahamd; Gates, J.C.; Gawith, C.B.E.; Smith, P.G.R.; Jaque, D. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Two-beam direct-UV-written silica-on-silicon waveguides have been investigated by confocal micro-luminescence experiments. The spatial and spectral analysis of the visible luminescence observed after 488 nm excitation has revealed the presence of various UV-induced defects due to the different compositions of core and under/over clad layers. The shape and waveguide's dimensions have been estimated from the spatial distribution of defect luminescence generated at the photosensitive core layer. The persistence of the defect luminescence induced in the core layer with increasing temperatures has been used to examine the thermal stability of two-beam UV-written waveguides as well as to determine the recombination energy of the corresponding luminescent defects.